2010
DOI: 10.17221/194/2008-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of shelled and kernel walnuts as affected by the moisture content

Abstract: Altuntas E., Erkol M. (2010): Physical properties of shelled and kernel walnuts as affected by the moisture content. Czech J. Food Sci., 28: 547-556.The variations in physical properties such as the size dimensions, unit mass, sphericity, projected area, bulk density, true density, volume, coefficient of friction on various surfaces, and terminal velocity of shelled and kernel walnuts as a function of the moisture content were determined. With an increase in the moisture content, the sphericity, projected area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
3
11
0
1
Order By: Relevance
“…In other words, drying will increase the ratio of air space volume to the solid volume within the system. This finding is similar to those of Chandrasekar and Viswanathan [34] for coffee; Paksoy and Aydin [54] for squash seeds; Altuntas and Erkol [55] for walnuts and De Souza Smaniotto et al [53] for sunflower seeds, and in contrast to Baryeh [46] for millet and Martins et al [56] for safflower grains who reported ρ b increased with the decrease in MC.…”
Section: Bulk Density True Density and Porositysupporting
confidence: 87%
“…In other words, drying will increase the ratio of air space volume to the solid volume within the system. This finding is similar to those of Chandrasekar and Viswanathan [34] for coffee; Paksoy and Aydin [54] for squash seeds; Altuntas and Erkol [55] for walnuts and De Souza Smaniotto et al [53] for sunflower seeds, and in contrast to Baryeh [46] for millet and Martins et al [56] for safflower grains who reported ρ b increased with the decrease in MC.…”
Section: Bulk Density True Density and Porositysupporting
confidence: 87%
“…The M e was taken to be 8% d.b. according to [5]. Every different drying temperature and air velocity took different time to achieve the M e , but in order to get the convenient results for the further analysis, the calculation of effective diffusivity was done on the same time basis of 1000 minute.…”
Section: Thin-layer Resultsmentioning
confidence: 99%
“…Walnuts should not be dried using temperatures higher than 43 °C, as the long-term exposure to higher temperatures could cause walnut oils to become rancid [5]. Thus, the highest drying temperature is limited to 40 °C.…”
Section: Investigation Aims and Drying Regimes Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various nut families/varieties have been investigated by several researchers due to the difficulty of extracting a nondamaged kernel from the shell. The focus of their research has been on the deformation characteristics of the shelled agricultural products such as various nut species/varieties (Adgidzi, Akande, & Dakogol, ; Altuntas & Erkol, ; Altuntas & Ozkan, ; Aviara, Onuh, & Ehiabhi, ; Bonisoli, Delprete, Sesana, Tamburro, & Tornincasa, ; Derafshi & Sharifian, ; Gharibzahedi, Mousavi, Hamedi, Khodaiyan, & Dadashpour, ; Guner, Dursun, & Dursun, ; Jennings & Macmillan, ; Koya & Faborode, ; Koyuncu, Ekinci, & Savran, ; Muniz, Freire, Soares, Cooke, & Guedes, ; Ozdemir & Ozilgen, ; Wang & Mai, ; Wang, Zhang, & Mai, ; Xu, Yan, Wang, & Liu, ). This previous research also highlights an important issue, which is that deformation orientation (loading/cracking position) has an important role for shelling, to be investigated.…”
Section: Introductionmentioning
confidence: 99%